Kekosongan Hukum dalam Pengelolaan Ruang Udara di Indonesia - Koloay, Jorry Soleman (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2021)
Indonesia’s airspace is a sovereign area with strategic value because it is utilized for various functions and dimensions of interest. As an inseparable part of the land, sea, and earth space, the air space should be arranged for security, safety, service, and prosperity. However, the absence of a law that underlies the management of air space, makes the interests of using air space overlap, not properly synchronized, and it seems that there is a lack of collaboration. This study uses a qualitative approach with content analysis methods, to discuss theories, analyze policies, and analyze expert opinions on the vacuum of airspace management policies in Indonesia, to then draw conclusions and recommendations. It is hoped that this study will be of use to efforts to formulate a very strategic and needed national airspace management policy.